Downregulation of Hlx Closely Related to the Decreased Expressions of T-bet and Runx3 in Patients with Gastric Cancer May Be Associated with a Pathological Event Leading to the Imbalance of Th1/Th2 - Yan Xu; Jingjing Gao; Zhaoliang Su; Xiaoli Dai; Yazhen Li; Yingzhao Liu; Jianguo Chen; Jia Tong; Yun Zhang; Chaoyang Wu; Dong Zheng; Shengjun Wang; et al. (Clinical and Developmental Immunology)
T-bet plays an important role in immunoregulation; it induces the differentiation of Th1 together with the homeobox transcription factor gene Hlx. Recent studies show that T-bet and Th1-associated factors are critical in regulating tumor development. However, the contributions of Hlx in the occurrence and development of cancer remain unknown. In this study, the Hlx, T-bet, Runx3, and IFN-γ were measured in PBMC from patients with gastric cancer and the correlation between Hlx and T-bet or IFN-γ was assessed. The expression levels of Hlx, T-bet, and IFN-γwere significantly decreased, and there was a positive correlation between Hlx and T-bet or IFN-γ. In addition, the Runx3 expression was also downregulated with the lower T-bet mRNA level. These results suggested that the decreased Hlx expression was closely associated with T-bet and Runx3 downregulations and may contribute to the development of gastric cancer.